Prevalence and characteristics of uveitis in the spondyloarthropathies: a systematic literature review. Issue 7 (25th October 2007) - Zeboulon, N; Dougados, M; Gossec, L
Abstract : Background: Uveitis is reported to be the most common extra-articular manifestation in spondyloarthritis (SpA); however, its prevalence and characteristics are not well established. Objective: To perform a systematic literature review in order to examine these topics. Methods: A systematic literature analysis was conducted in the Medline database up to October 2006 and in the abstracts of rheumatology scientific meetings for the years 2004, 2005 and 2006. A hand search of references was also performed. Articles were analysed if they reported the prevalence or characteristics of uveitis in SpA. Data abstraction was standardised. Statistical analysis was mainly descriptive. Results: Among the 957 articles selected by the search, 126 articles (29 877 patients) allowed a calculation of the prevalence of uveitis in SpA; 36 articles (1989 patients) described its characteristics. The mean (SD) prevalence of uveitis was 32.7 (0.5)%; it varied with the type of SpA—for example, 33.2 (0.8)% for ankylosing spondylitis versus 25.1 (2.3)% for psoriatic arthritis. This prevalence increased with mean disease duration and was higher in HLA-B27-positive patients with an odds ratio of 4.2. Uveitis was acute in 88.7 (2.5)%, anterior in 90.5 (2.0)%, unilateral in 87.3 (2.8)%. Recurrence occurred in 50.6 (2.6)% and a reduction of visual acuity was observed in 8.3 (3.8)%. Conclusion: The prevalence of uveitis varies with disease duration and according to the type of SpA. Reduction of visual acuity is not exceptional. Because of recent promising data about the effects of anti-tumour necrosis factor therapy on uveitis flares in SpA, it was important to determine this baseline prevalence.